Activating transcription factor 3 (ATF3) as a perspective biomarker of Crohn's disease. (July 2020) - Kobayashi, Nobuyuki; Arihiro, Seiji; Shimada, Kazuya; Hoshino, Atsushi; Saijo, Hiroki; Oka, Naomi; Saruta, Masayuki; Kondo, Kazuhiro
Introduction: Inflammatory bowel disease (IBD) is characterized by chronic inflammation of the intestinal tract. Known types are Crohn's disease (CD) and ulcerative colitis (UC), but their cause remains unclear and there is no convenient biomarker for IBD. The present study aimed to demonstrate an association between the onset of CD and activating transcription factor 3 (ATF3); as a new biomarker, measurement of blood ATF3 mRNA would be useful for distinguishing between CD and UC. Methods: First, in a mouse model of IBD in which damage to the intestinal mucosa was chemically induced with dextran sulfate sodium (DSS), intestinal ATF3 mRNA was evaluated. Next, in human subjects, CD and UC patients, blood ATF3 mRNA and intestinal ATF3 protein production were evaluated. Results: In the mouse model of IBD, intestinal ATF3 mRNA was elevated compared with the control ( P < 0.0001). In CD patients, blood ATF3 mRNA was elevated as compared with normal controls (NCs) and UC patients ( P < 0.05). In addition, we observed an increase in ATF3 production in the intestinal tract specific to CD. Conclusion: ATF3 is involved in the onset of CD, and blood ATF3 mRNA measurements would be useful for distinguishing it from UC.